Fungsi Pengunyahan dan Gangguan Kognitif Terkait Kehilangan Gigi Pada Lansia - Rani Rahayu, Elma; Asia, Rr. Asyurati; Ayu Ratih Utari Mayun, I Gusti (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Aging causes various changes, including in the oral cavity tissues. The WHO recommends that elderly individuals aged ≥ 60 years should have at least 20 functional teeth to support their quality of life. Tooth loss in the elderly affects chewing function, psychological well-being, and cognitive function. Objectives: To determine the relationship between tooth loss in the elderly on masticatory function and cognitive impairment. Conclusion: Older adults with >12 missing teeth are more vulnerable to decreased masticatory function and cognitive impairment.